2020
DOI: 10.1155/2020/8625842
|View full text |Cite
|
Sign up to set email alerts
|

Oral Rehabilitation with Removable Partial Denture of a Patient with Cleidocranial Dysplasia

Abstract: This case report describes the oral rehabilitation of a patient with cleidocranial dysplasia who received a removable partial denture along with silicone-based permanent soft liner to improve esthetic and masticatory function. This patient was the candidate of neither implant nor orthodontic treatment due to medical conditions, history of mandible fracture, age, and risk of fracture after mandibular teeth extractions. Cone-beam computed tomography has made it possible to obtain comprehensive information regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…In the 6th month, all the surfaces showed significant differences in the mean surface hardness with p<0.005 except for Polident and Group I control. These results were consistent with the studies of (Tasopoulos et al 2023) and (Ghomi et al 2020), where the authors reported a higher surface hardness of Periogard, followed by Polident and Secure. Concerning the comparison of the surface roughness in two denture materials, Voco and Mollosil, it was seen that in the control group, the values were higher for the Mollosil group compared to Voco, which were statistically nonsignificant in the 1st week, 1st month, and 6th month, corresponding to p values of 1.000, 0.414, and 0.492, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In the 6th month, all the surfaces showed significant differences in the mean surface hardness with p<0.005 except for Polident and Group I control. These results were consistent with the studies of (Tasopoulos et al 2023) and (Ghomi et al 2020), where the authors reported a higher surface hardness of Periogard, followed by Polident and Secure. Concerning the comparison of the surface roughness in two denture materials, Voco and Mollosil, it was seen that in the control group, the values were higher for the Mollosil group compared to Voco, which were statistically nonsignificant in the 1st week, 1st month, and 6th month, corresponding to p values of 1.000, 0.414, and 0.492, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…underdevelopment of the maxilla 45,[47][48][49] . Panoramic X-rays and tomography show multiple impacted permanent teeth 47,49 .…”
Section: Crouzon Syndromementioning
confidence: 99%
“…underdevelopment of the maxilla 45,[47][48][49] . Panoramic X-rays and tomography show multiple impacted permanent teeth 47,49 . Diagnosis is usually based on clinical and radiological findings 47 .…”
Section: Crouzon Syndromementioning
confidence: 99%
See 2 more Smart Citations